Host Specificity of Snodgrassella in Eastern and Western Honeybees and Its Effects on Naturally Occurring Deformed Wing Virus Titers - Nihong Zhou; Shangning Yang; Ruike Wei; Fuliang Hu; Dandan Liu; Huoqing Zheng (Insects)
Honeybee gut microbiota undergoes long-term adaptive evolution with the host, resulting in host-specific genomic and functional characteristics. However, the specific role of host-specialized strains in shaping host physiological functions remains understudied. This study investigates the host specificity of the core gut symbiont Snodgrassella in A. cerana and A. mellifera, exploring its effects on immune response and natural virus suppression through genomic analysis and colonization experiments. Genomic analysis revealed that strain from A. mellifera, exhibited a larger genome and greater gene content compared to strain from A. cerana. Competitive colonization experiments showed that although strains from different origins had similar colonization efficiency in the host, host-specific strain displayed a clear home-field advantage in the competitive colonization process. Moreover, Inoculation of A. mellifera with its native Snodgrassella strain significantly reduced Deformed Wing Virus (DWV) titers, whereas a non-native strain had no effect. In contrast, neither strain altered DWV or Sacbrood Virus (SBV) levels in A. cerana. Immune gene analysis revealed that only the native Snodgrassella strain upregulated defensin 2 in A. mellifera, while no significant changes occurred in A. cerana with either strain. These results suggest that Snodgrassella exhibits host specificity at the strain level, influencing both host immune response and virus suppression, with non-native strains showing reduced efficacy in these functional roles, especially in A. mellifera.